2021
DOI: 10.21203/rs.3.rs-779229/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization and complete genome sequence of bacteriophage vB_Vc_SrVc2, a marine phage that infects Vibrio campbellii

Abstract: Vibrio campbellii is widely distributed in the marine environment and is an important pathogen of aquatic organisms such as shrimp, fish, and mollusks. The emergence of multi-drug resistance among these bacteria resulted in a worldwide public health problem, which requires alternative treatment approaches such as phage therapy. In the present study, we isolated a phage vB_Vc_SrVc2 from white shrimp hepatopancreas with symptoms of AHPND. Phage vB_Vc_SrVc2 is a member of the genus Maculvirus and the family Autog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…According to earlier studies, OPA17 is different from other V. campbellii phages. In a previous study, lytic phages vB_Vc_SrVc2 and vB_Vc_SrVc9, which infect V. campbellii , were classified as members of the Autographiviridae family ( 4 , 25 ). However, the potential of Siphoviridae phage to control of luminous vibriosis caused by V. harveyi in shrimp aquaculture has been reported in many previous studies ( 3 , 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to earlier studies, OPA17 is different from other V. campbellii phages. In a previous study, lytic phages vB_Vc_SrVc2 and vB_Vc_SrVc9, which infect V. campbellii , were classified as members of the Autographiviridae family ( 4 , 25 ). However, the potential of Siphoviridae phage to control of luminous vibriosis caused by V. harveyi in shrimp aquaculture has been reported in many previous studies ( 3 , 28 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of phages to infect different species within the genus Vibrio , especially among Harveyi clade species, has been reported in previous studies. V. campbellii phages vB_Vc_SrVc2 and vB_Vc_SrVc9 isolated from the hepatopancreas of shrimp with AHPND in Mexico also lysed V. parahaemolyticus and V. alginolyticus ( 4 , 25 ). Other studies showed the cross-infectivity of isolated phages among Harveyi clade hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation